KULTOUR La María: red arquitectónica de centros para manifestaciones culturales en Cartagena de Indias (2018)
The artistic expression like dance and music in Cartagena de Indias are one of the cultural activities more representatives of the city, therefore, have an appropriate place designed to the realization for those activities is really important for their execution. As a first measure an analysis of the city is carry out through situational flow chart or problem tree, where is formed the proposal of the investigation and which it is based on the same theoretical, referential, historical and legal framework. In the macro scale it is proposed a concise outline of the distribution between urban-architectural spaces that encompass the entire Cartagena city; in the meso scale, it is projected a design where the point of their realization is feasible. And inally, for the micro scale is carried out to the realization of the research project, an architectural center for cultural events in Cartagena de Indias, KULTOUR La María